Cultural narratives on screen: The construction of Yogyakarta cultural values in local short films - Setiawan, Benni; Suwarto, Dyna Herlina; Adikara, Gilang Jiwana (Jurnal Komunikasi, 2026)
This study examines Yogyakarta short films construction on local cultural values through narrative structure using a qualitative narratological approach based on Tzvetan Todorov’s model. Analyzing 21 province government-funded short films, the study focuses on protagonists, conflict, and resolution as key narrative elements. The findings show that these films consistently position wong cilik as protagonists whose conflicts arise from everyday social relations, including family obligations, economic constraints, and community dynamics. Disruptions are typically externally driven, while resolution is achieved through restraint, negotiation, and relational adjustment rather than confrontation. This produces a non-confrontational narrative strategy, often expressed through openended endings that emphasize reflection and social equilibrium. These patterns are reinforced by minimal dialogue, silence, non-professional actors, and slow pacing. Together, these elements demonstrate non-confrontational storytelling operates as the primary narrative structure.